2023
DOI: 10.1111/jfpe.14341
|View full text |Cite
|
Sign up to set email alerts
|

Microwave treatment effect on functional and pasting properties, and storage stability of white finger millet

Abstract: Microwave (MW) treatment is a promising technique in cereal processing to improve nutritional quality. The present study investigated the effect of MW power level and exposure time on white finger millet flour (WFMF). Nine different MW treatment combinations were taken based on power level (720 W, 840 W, and 900 W), and exposure time (2 min, 4 min, and 6 min), after the MW treatment the flours are stored at 45 C for 15 days for storage study. The physicochemical, functional, pasting properties, and storage sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Other studies have found a similar darker color in MWtreated sorghum, corn flour, and white finger millet Ananthu et al, 2023).…”
Section: Colorsupporting
confidence: 60%
See 4 more Smart Citations
“…Other studies have found a similar darker color in MWtreated sorghum, corn flour, and white finger millet Ananthu et al, 2023).…”
Section: Colorsupporting
confidence: 60%
“…As a result, weaker interactions could have formed with partially damaged or swelled starch granules, proteins, and lipids, thereby reducing the PV (Kamble et al., 2020). Furthermore, the loss of double‐helix order structure during MW treatment due to the degradation of existing double bonds and the formation of new double bonds in carboxyl and hydroxyl groups could have contributed to the lower PV (Ananthu et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations